Determining psychometric properties of achievement tests in ODL business management (2010)
The study sought to expose ODL educators to the challenges of constructing achievement tests in distance learning school of business management. A pool of one hundred test items were drawn and administered on two hundred respondents, who were purposively selected among the University of Lagos distance learning Business Managementstudents. The data collection instrument used was Business Management Achievement Test (BMAT). The discrimination and difficulty level of the test items were determined and the instrument was subjected to content and concurrent validity and Kuder- Richardson formula 20 was used to ascertain its reliability. The results showed that 48% of the test items were moderately difficult and discriminated well among the examinees, 12% of the items were too difficult, while 40% of the items were too simple for the testees. The study found out that the instrument was 0.94 reliable and valid (0.78 for content and 0.76 for concurrent). The implications of the findings were discussed with a view to exposing distance educators to the challenges involved in constructing a valid and reliable test.